2007
DOI: 10.1159/000101286
|View full text |Cite
|
Sign up to set email alerts
|

Defining Growth Hormone Status in Adults with Hypopituitarism

Abstract: The identification of adults with severe growth hormone (GH) deficiency (GHD) is not straightforward. The insulin tolerance test remains the gold standard diagnostic test, although other stimuli such as GH-releasing hormone-arginine are gaining acceptance. Insulin-like growth factor-I has a poor diagnostic sensitivity in adult-onset GHD, but is more useful in the subgroup of adults with childhood-onset GHD. Therapeutic developments include increasing recognition of the need to continue GH therapy beyond final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 139 publications
0
5
0
Order By: Relevance
“…Gynaecologists, having established that the male partner is fertile, consider a woman to be infertile if the woman has not conceived after twelve months of contraceptive free intercourse, if the female is under the age of 34, or the woman has not conceived after six months of contraceptive free intercourse if the female is over the age of 35 [2]. Primary infertility describes a state in which a woman has never been able to conceive [3]. Between 8 and 12 percent of couples around the world have difficulty conceiving a child at some point in their lives, and in some areas, the figure reaches one-third or more [4].…”
Section: Introductionmentioning
confidence: 99%
“…Gynaecologists, having established that the male partner is fertile, consider a woman to be infertile if the woman has not conceived after twelve months of contraceptive free intercourse, if the female is under the age of 34, or the woman has not conceived after six months of contraceptive free intercourse if the female is over the age of 35 [2]. Primary infertility describes a state in which a woman has never been able to conceive [3]. Between 8 and 12 percent of couples around the world have difficulty conceiving a child at some point in their lives, and in some areas, the figure reaches one-third or more [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have yielded evidence to support the efficacy of GH in preventing the adverse changes in body composition (26,30,31). Thus, the practice of discontinuing GH in all patients after attainment of adult height is under review and it is suggested that continuation of GH replacement in GHD individuals during the post-pubertal 'transition' phase may alleviate the metabolic complications of GH deficiency, including maturation of bone (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, circulating GH levels are negatively correlated with body mass index. 63,64 Obese patients also show a blunted or absent response to all known GH stimuli, [65][66][67][68][69][70][71] where in some cases these changes can be difficult to differentiate from organic GH deficiency (GHD). 71 Significant weight loss (by exercise/diet or gastric bypass) results in the recovery of circulating GH concentrations.…”
Section: Effects Of Nutrient Excess (Obesity) On Gh/igf-imentioning
confidence: 99%
“…63,64 Obese patients also show a blunted or absent response to all known GH stimuli, [65][66][67][68][69][70][71] where in some cases these changes can be difficult to differentiate from organic GH deficiency (GHD). 71 Significant weight loss (by exercise/diet or gastric bypass) results in the recovery of circulating GH concentrations. [72][73][74] Therefore, the metabolic alterations associated with weight gain are thought to be the precipitating events leading to suppression of the GH-axis.…”
Section: Effects Of Nutrient Excess (Obesity) On Gh/igf-imentioning
confidence: 99%